1988
DOI: 10.1136/thx.43.10.756
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium cromoglycate and nedocromil sodium on histamine secretion from human lung mast cells.

Abstract: Sodium cromoglycate and nedocromil sodium produced a dose dependent inhibition of histamine secretion from human pulmonary mast cells obtained by bronchoalveolar lavage and by enzymatic dissociation of lung parenchyma. Both compounds were significantly more active against the lavage cells than against the dispersed lung cells, and nedocromil sodium was an order of magnitude more effective than sodium cromoglycate against both cell types. Tachyphylaxis was observed with the parenchymal cells but not with the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(62 citation statements)
references
References 12 publications
4
58
0
Order By: Relevance
“…Although several investigators have demonstrated that nedocromil sodium can inhibit the activation of different inflammatory cell types, including mast cells, eosinophils, monocytes, macrophages and platelets in vitro [23][24][25][26][27], the precise mode of action of this drug has only recently become clear. Studies have demonstrated that both sodium cromoglycate [28] and nedocromil sodium [29] block a chloride ion channel in rat basophil leukaemia cells, and have suggested that inhibition of this or a similar channel may inhibit mast cell activation, since influx of chloride ions into the mast cell is in part a prerequisite for calcium influx [30] and subsequent activation of this cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Although several investigators have demonstrated that nedocromil sodium can inhibit the activation of different inflammatory cell types, including mast cells, eosinophils, monocytes, macrophages and platelets in vitro [23][24][25][26][27], the precise mode of action of this drug has only recently become clear. Studies have demonstrated that both sodium cromoglycate [28] and nedocromil sodium [29] block a chloride ion channel in rat basophil leukaemia cells, and have suggested that inhibition of this or a similar channel may inhibit mast cell activation, since influx of chloride ions into the mast cell is in part a prerequisite for calcium influx [30] and subsequent activation of this cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Nedocromil sodium is a pyranoquinoline dicarboxyline acid which has been demonstrated to have some beneficial effects in various models of asthma, including human airway response to hyperosmolar challenge [488], PAF-mediated bronchoconstriction [489], early and late responses to allergen challenge in asthmatics [490,491], and eosinophil recruitment in humans [491]. Besides its inhibitory action on mast cells, neutrophils, monocytes and platelets [492][493][494][495][496], nedocromil sodium has been shown to block various eosinophil functions, including secretion of granule proteins [497], eosinophil chemotaxis [498,499], surface antigen expression [500], leukotriene C 4 secretion in response to various agents [499,501] as well as density change, damage to airway epithelium [502,503] and other cytotoxic mechanisms [498,500]. Hence, these inhibitory effects of nedocromil on eosinophil function suggest that it may be effective in eosinophil-related disease, such as asthma.…”
Section: Xanthines and Selective Phosphodiesterase Inhibitorsmentioning
confidence: 99%
“…during MBS airway challenge, we examined the effects of nedocromil sodium and of frusemide which are both able to inhibit the release of histamine or leukotrienes from inflammatory cells (Leung et al, 1988;Bruinjzeel et al, 1989;Anderson et al, 1991).…”
Section: Introductionmentioning
confidence: 99%